Wariograf - jedna z metod praktyki śledczo-sądowej = Polygraph - one of the method crime detection and judicial practice - Klimczyk, Agata (Journal of Education, Health and Sport, 2015)
Klimczyk Agata. Wariograf - jedna z metod praktyki śledczo-sądowej = Polygraph - one of the method crime detection and judicial practice. Journal of Education, Health and Sport. 2015;5(9):375-379. ISSN 2391-8306. DOI10.5281/zenodo.30939 http://dx.doi.org/10.5281/zenodo.30939 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A375-379 https://pbn.nauka.gov.pl/works/624393 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 12.09.2015. Wariograf - jedna z metod praktyki śledczo-sądowej Polygraph - one of the method crime detection and judicial practice Agata Klimczyk Nicolaus Copernicus University in Toruń Streszczenie Celem publikacji jest przedstawienie jednej z metod badań kryminalistycznych- wariografu. W pracy dokonano analizy aktów prawnych, w celu prześledzenia zagadnień dotyczących opisywanego tematu. Przeprowadzono analizę specjalistycznego piśmiennictwa. Wskazano, ze wariograf jest jedną z metod pozwalających na rejestrowanie więzi emocjonalnych badanego do ludzi, rzeczy, zjawisk, zdarzeń itp. Stwierdzono, że wariografia kryminalistyczna jest kontrowersyjną metodą, może przyczynić się do wzrostu wykrywalności przestępstw oraz do oczyszczenia z zarzutów osób niewinnych. Słowa kluczowe: kryminalistyka, wariograf, badania, prawo. Abstract The main aim of this work is to show one of the crime detection method- polygraph. In the work was used special literature and legal regulations. It indicated that the polygraph is one of the methods which record the audited emotional ties to the people, things , events , incidents ect. Main conclusions are related that forensic polygraph is controversial method wchih can contribute to an increase in crime detection and could clear of the allegations of innocent people. Key words: crime detection, polygraph, research, law.